Structure and development of the Czech wine market and foreign wine trade - Kamila Vesela; David Křížek; Lucie Severova (Wine Economics and Policy, 2023)
The aim of the presented text is to evaluate the structure and development of the Czech wine market, foreign wine trade and to analyse the factors shaping domestic demand for wine. The text presents the results of the analysis of primary and secondary data. Time series on the development and direction of the foreign wine trade are analysed and the results are then compared with the findings of a questionnaire survey of 946 respondents which provides information about the current consumer preferences of the Czech population in drinking wine. Wine consumption has shown stable growth over the last 20 years, as demonstrated by primary research. The research has proven that wine consumption in the Czech Republic shows a faster growth rate than domestic production, which is also reflected in import demand. From the point of view of factors influencing domestic demand for wine, it is mainly the age, education, income and size of the consumer's residence. The research provides an up-to-date view of the structure of wine demand in the Czech Republic and identifies the factors influencing wine demand. The research also makes it possible to predict the future direction of the Czech wine trade.
Keywords: 330; export; import; production; consumption; wine